Implementation of Knowledge Management on Hotel and Spa GSA Employee Performance - I Putu Gde Jayendra Praditya; I Ketut Suarja; Ni Gusti Nyoman Suci Murni (Catuspata Press, 2020)
Purpose: This research is to know the implementation of Knowledge Management conducted by the management of a 5 star hotel and spa in Nusa Dua tourist area, Badung, Bali, Indonesia, for its Guest Service Agent employees. Research methods: The total respondent on this research is 10 which are Guest Service Agent employees and analysis by using SPSS 25.0. Analyze technique used is a multiple linear regression with personal knowledge, job procedure, and technology as an independent variable and employee performance as a dependent variable. Findings: Knowledge Management was is effective to improve the employee performance in the hotel researched. The technology variable has a significant effect on the performance of the guest service agent employees, as well as the variables of personal knowledge, job procedures and technology simultaneously positively influencing the performance of guest service agent employees. Implication: The management needs to pay more attention to the Knowledge Management that has been done and if possible it can be increased again